Digital technology use, technological perception, and farmers’ adoption behavior of green control technology: evidence from Sichuan Province, China - Yin, Xiyang; Weng, Junming; Li, Wanyi; Sun, Jinyang (Frontiers in Sustainable Food Systems, 2025)
The lack of technical information is widely regarded by researchers as a significant barrier to the promotion of green technologies. However, with the extensive application of Digital Technology (DT) in the rural and agricultural sectors, the way information is transmitted in rural areas has undergone a fundamental transformation, which also brings an opportunity for the promotion of green agricultural technologies. Taking Green Control Technology (GCT) as an example, based on the survey data of rural households in Sichuan, China, this study empirically examines the association between the use of DT and the adoption of GCT using a binary Probit model. Results indicate that, the use of DT significantly promotes the adoption of GCT among farmers, leads to an average increase of about 16.1%. During this process, farmers’ perceived usefulness, perceived ease of use, and perceived risk of GCT serve as mediators, the mediation effect accounted for 45.05, 35.13, and 17.09%, respectively. The impacts of DT also vary across groups, with younger farmers, those operating on smaller scales, and those residing closer to the county benefiting more. The study suggests strengthening the construction of rural digital infrastructure, improving the digital literacy of farmers, and increasing the digital promotion of GCT.